Deletion of cscR in Escherichia coli W improves growth and poly-3-hydroxybutyrate (PHB) production from sucrose in fed batch culture - Arifin, Yalun; Sabri, S.; Sugiarto, H.; Krömer, J.; Vickers, C.; Nielsen, L. (Elsevier Science, 2010)
Sucrose has several advantages over glucose as a feedstock for bioprocesses, both environmentally and economically. However, most industrial Escherichia coli strains are unable to utilize sucrose. E. coli W can grow on sucrose but stops growing when sucrose concentrations become low. This is undesirable in fed-batch conditions where sugar levels are low between feeding pulses. Sucrose uptake rates were improved by removal of the cscR gene, which encodes a protein that represses expression of the sucrose utilization genes at low sucrose concentrations. Poly-3-hydroxybutyrate (PHB) was used as a model compound in order to assess the effect of improved sugar utilization on bio-production. In the cscR knockout strain, production from sucrose was improved by 50%; this strain also produced 30% more PHB than the wild-type using glucose. This result demonstrates the feasibility of utilizing sucrose as an industrial feedstock for E. coli-based bioprocesses in high cell density culture. © 2011.